Peran Pemimpin dalam Pencapaian Kinerja Pegawai (Studi pada Badan Kepegawaian Daerah Kota Malang) - Armhela Fazrien (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2014)
Abstract: The Role of Leader in Employee Performance Achievement (Studies in Employment Board Regional Malang). In the organization of human interaction are incorporated in them, such as the relationship with subordinate leaders, that they will work together in performing the tasks that have been planned to achieve organizational goals. A leader in the proficient and skilled capable expected should also be willing and have the willingness to work effectively and efficiently. The task of a leader is to plan, mobilize and supervise every activity in the organization. One of the main tasks of a leader is to be able to achieve the performance of employees which in turn can achieve the goals and objectives of the organization are in leader. The method used in this research is descriptive qualitative approach His research focus is 1) the role of the leader in achieving the performance of employees at the Regional Employment Board of Malang. 2) the performance of employees in the Regional Employment Board of Malang. The results showed that the role of the leader in achieving the performance of employees in Malang Regional Employment Board can already be quite well where leaders are able to carry out their role so as to achieve better performance of employees in order to realize the objectives of the organization. Keywords: Leader, Employee Performance Â Abstrak: Peran Pemimpin Dalam Pencapaian Kinerja PegawaiÂ (Studi Pada Badan Kepegawaian Daerah Kota Malang). Dalam organisasi terdapat interaksi manusia yang tergabung di dalamnya, seperti hubungan pemimpin dengan bawahan, yang keduanya akan bekerja sama dalam melaksanakan tugas yang sudah terencana untuk mencapai tujuan organisasi. Tugas dari seorang pemimpin yaitu merencanakan, menggerakkan dan mengawasi setiap aktivitas dalam organisasi. Salah satu tugas utama dari seorang pemimpin adalah harus bisa mencapai kinerja pegawai sehingga pada akhirnya dapat mencapai tujuan dan sasaran dari organisasi yang di pimpinnya. Jenis penelitian yang digunakan pada penelitian ini adalah deskriptif dengan pendekatan kualitatif. Fokus Penelitiannya adalah 1) peran pemimpin dalam pencapaian kinerja pegawainya pada Badan Kepegawaian Daerah Kota Malang. 2) kinerja pegawai pada Badan Kepegawaian Daerah Kota Malang. Hasil penelitian menunjukkan bahwa peran pemimpin dalam mencapai kinerja pegawai pada Badan Kepegawaian Daerah Kota Malang sudah dapat dikatakan cukup baik dimana pemimpin sudah bisa melaksanakan perannya dengan baik sehingga dapat mencapai kinerja pegawai lebih baik dalam rangka mewujudkan tujuan dari organisasi. Kata Kunci: Pememimpin, Kinerja PegawaiÂ